Make or wreck Vegetations in heritage architectural ruins - Malaga, Juanito Montallana (College of Architecture, University of the Philippines Diliman, 2010)
The Spanish occupation of the Philippines a few centuries ago gave the country countless architectural treasures. In every province, there are found prominent structures of different types such as government buildings, cathedrals, churches, and small visitas; cemetery entrances and capillas (chapels); bridges; and majones (boundary and bridge markers), among others. However, these structures vary in current states; some are still in good conditions like most of the bridges and the churches; some need urgent repair, major and minor alike, like the churches and a number of bahay na bato (stone house); and still some are in the state of ruins like most of the structures all around the country. The situation is also true in countless number of countries, some with world-renowned architectural ruins that are with high risk of disappearance. Particular of these are the Angkor War of Cambodia, the Borobudur in Indonesia, the pyramids of Mexico, and the countless temples of India; with their iconic magnificence in built and appearance, yet threatened by the invasion of the forest outgrowth while at the same time, apparently adding value to the site. In the Philippines and in other countries , the problem of vegetation outgrowth impacts on old architectural treasures. On one side, there are claims that these outgrowths are invasive and destructive as such, measures should be taken to get rid of them and prevent eventual destruction of these heritage structures. On the other hand, there are views that this vegetation embellishes and puts added value to the scenic character of the ruins. This paper will look into the cases of two notable Heritage Architectural Ruins in Albay, Philippines to determine the context of vegetation outgrowth relative to its destructive and beneficial aspects. It will attempt to formulate a framework that will aid in weighing up the positive and negative effects of vegetation in ruins. The paper argues that the strategic scheme in determining these effects could help in the preservation of heritage architectural treasures, thereby highlighting their significance and making them more enduring.